Enhancing power quality in wireless DC power supplies through active power filtering: A computer simulation approach - Baharom, Rahimi; Bunyamin, Wan Muhamad Hakimi Wan (International Journal of Power Electronics and Drive Systems (IJPEDS), 2024)
This paper presents a computer simulation model for a high-power factor wireless DC power supply system, integrating an active power filter (APF) at the rectifier stage on the transmitter side using a rectifier boost technique. The APF, employing a MOSFET switch regulated by active pulse width modulation (APWM) within a current control loop, addresses pulsating and distorted AC supply currents caused by non-linear loads. A robust closed-loop control mechanism, including a subtractor circuit, proportional-integral (PI) controller, and comparator, ensures the generation of a continuous sinusoidal waveform synchronized with the supply voltage. The model utilizes a high-frequency inverter to convert DC to AC, which is then wirelessly transmitted via wireless power transfer (WPT) technology and converted back to DC by a high-frequency rectifier. MATLAB/Simulink simulation results show a significant reduction in total harmonic distortion (THD) of the AC supply current, complying with IEEE 519 standards. Selected results are presented to verify the proposed method's effectiveness in reducing harmonic distortions and enhancing power quality. This study highlights the advantages of WPT in scenarios where traditional wired connections are impractical and underscores the potential of this system for real-world applications, particularly in developing high-power factor wireless DC power supply systems.